2019
DOI: 10.24059/olj.v22i4.1384
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Learning Engagement with Online Students

Abstract: University students are increasingly demanding that traditionally taught courses are converted to an online platform. While quality standards are in place for the format and organization of online courses, professors often are left wondering what activities contribute to learning engagement for their online students. The research question driving this study was, what activities contribute to learning engagement for online students? To investigate this question, an online survey was conducted in one state unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 29 publications
4
71
1
1
Order By: Relevance
“…Essentially, any strategy used to assist in making students feel engaged and connected with each other and the instructor (Lowenthal, 2010) is considered social presence. Both student-student interaction and student-instructor interaction can influence students' engagement in online learning (Buelow et al, 2018;Purarjomandlangrudi et al, 2016). Specifically, they are more engaged in learning when able to interact with the instructor and other students (Dixon, 2010;Holzweiss et al, 2014).…”
Section: Social Presencementioning
confidence: 99%
See 1 more Smart Citation
“…Essentially, any strategy used to assist in making students feel engaged and connected with each other and the instructor (Lowenthal, 2010) is considered social presence. Both student-student interaction and student-instructor interaction can influence students' engagement in online learning (Buelow et al, 2018;Purarjomandlangrudi et al, 2016). Specifically, they are more engaged in learning when able to interact with the instructor and other students (Dixon, 2010;Holzweiss et al, 2014).…”
Section: Social Presencementioning
confidence: 99%
“…First, although social presence was important to both students and faculty, students seemed to put a greater emphasis on student-student interaction whereas faculties were more concerned with faculty-student interaction. Research has found that both types of interactions are important when it comes to online course engagement (Buelow et al, 2018;Purarjomandlangrudi et al, 2016) with some research pointing to students valuing student-instructor relationships over student-student relationships (Martin & Bolliger, 2018). Future research should seek to better understand the specific roles these different relationships play in creating engaging online learning environments and how to best foster them throughout an online course.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…A non-traditional student is between the ages of 20-65, has several social roles in life and might be working full time. Online learning provides these students with greater access to formal learning environments from which they are physically distant and the flexibility to start their learning journey at any time while being able to work and study (Buelow et al, 2018). With the pandemic, online learning provides all students with the ability to continue their studies, so that they can complete their programmes within the original time-frame and with minimal interruption.…”
Section: Introductionmentioning
confidence: 99%
“…Engaging students, whether in a face-to-face classroom or through an online programme, is considered a critical factor in the academic success of students (Buelow et al, 2018). Learner engagement occurs through their behaviours, their emotions and their cognition (Astin, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation